Eye-brain connection: an altered profile of spatial attention in myopia - De Lestrange-Anginieur, Elie; Pan, Feng; Thompson, Benjamin; Wong, Kin Yau (Frontiers in Neuroscience, 2025)
BackgroundRefractive errors represent an important cause of visual impairment, impacting the quality of vision in billions of people across the globe. Degraded visual input may cause individuals with refractive errors to deploy greater attentional resources during visual tasks. We tested the hypothesis that myopia alters the pattern of visual attention.MethodsTwenty participants (10 near-emmetropes) performed an acuity discrimination task at random visual field locations (eccentricity range: 1–10°; spacing: 1°; polar coordinates of 0°, 90°, 180°or 270°) under conditions of neutral attention (no information on the stimulus position) and focused attention (target presentation in a single meridian), while fully optically corrected. The spatial distribution of attention-related modulation was estimated by the ratio of performance between the focused and neutral conditions across spatial eccentricities using acuity resolution (primary outcome) and reaction times (RT), as measures of attention.ResultsUse of linear mixed models revealed that the enhancing effect of attention follows a cubic spatial profile for acuity and RT, indicating a finite attentional window in myopes and emmetropes with a peak eccentricity at around 4°. Significant dependence of attention modulation on polar coordinate and refractive status was also identified (for both acuity and RT), with larger attention enhancement at the South position, compared to the North location, and lower attention efficiency in myopes, as compared to emmetropes across the visual field. Our modeling of attention-related modulation in acuity further indicated that myopes experience narrower attentional windows, suggesting a reallocation of cognitive resources.ConclusionThe study is the first, to our knowledge, to provide a detailed spatial profile of attention-related modulation linked to mild to regular myopia, highlighting a differential shape of the focus of attention with refractive status, which demonstrates a redistribution of attention with myopia. This revealed a link between myopia and visual attention, which requires further investigation.